PENGARUH PENERAPAN METODE DEMONSTRASI TERHADAP KETERAMPILAN MEMBACA PUISI ANAK PESERTA DIDIK SEKOLAH DASAR - Cici Sri Widya Agustina; Syambasril Syambasril; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe the effect of the application of the demonstration method on poetry reading skills of students in grade IV 39 Primary Schools in Pontianak Kota. The method used is an experimental method with a form of Nonequivalent Control Group Design. The population in this study were all students of grade IV 39 Primary Schools in Pontianak Kota. The sample in this study was class IV B totaling 30 as a control class and class IV C totaled 31 as an experimental class. The data collection technique used is the measurement technique with measurement tools. Then an analysis based on the results of the post-test used the t-test. The research results obtained t count (4.3057)> t table (2.056), then Ha is accepted. This shows that there is an influence of the application of the demonstration method to the poetry reading skills of students in grade IV 39 Primary Schools in Pontianak Kota. From the calculation of the effect size the ES is 1,19418 (high category). This means that learned by applied the demonstration method gives a high effect on poetry reading skills of students in grade IV 39 Primary Schools in Pontianak Kota. Keywords: Demonstration Method, Poetry Reading Skills.